Does Irrigation Mediate Inclusiveness in Education? A Study of Two Villages in Hyderabad and Karnataka. (September 2020) - Scaria, Suma
This study basically tries to understand how far sources of irrigation mediate development outcomes relating to education. This micro-level study based on a comparative study of both canal-irrigated and non-canal-irrigated villages in the Hyderabad–Karnataka region shows that public irrigation plays a major role in achieving inclusiveness in education, especially higher education. Unlike a non-canal-irrigated village, in a canal-irrigated village, along with ' dominant castes, a few Scheduled Castes (SCs) also have access to higher education. The access to 'quality education', in terms of private institutions and English medium schools, is also inclusive in canal-irrigated villages. On the other hand, access to education is limited to big landowners in a non-canal-irrigated village. However, a gender-wise analysis shows that the above inclusiveness in canal-irrigated villages regarding access to education has failed to reach women. Such outcomes in education are explained in terms of landownership pattern, private investment in irrigation and gendered access to education.